Effects of irbesartan on myocardial injury in diabetic rats: The role of NLRP3/ASC/Caspase-1 pathway. (May 2020) - Rong, Li; Sun, Shuo; Zhu, Feiyu; Xu, Qingmei; Li, Hui; Gao, Qin; Zhang, Wei; Tang, Bi; Zhang, Heng; Wang, Hongju; Kang, Pinfang
To observe the mechanism of myocardial injury in diabetic rats after irbesartan intervention and analyze the role of nucleotide binding oligomerization domain-like receptor protein 3 (NLRP3) inflammatory pathway. The experiment was divided into four groups: normal control group (CON), high glucose and high caloric diet group (HC), diabetes group (DM) and diabetes+irbesartan group (DM+Ir). Compared with CON group, in HC group, triglyceride, total cholesterol and fasting blood glucose levels were increased; however, there was no significant difference of the cardiac function, the degree of myocardial fibrosis, NLRP3, ASC, Caspase-1 mRNA and protein expressions and the releasing of inflammatory factors interleukin (IL)-1β and IL-18. Compared with HC group, in DM group, triglyceride, total cholesterol, fasting blood glucose, IL-1β and IL-18 levels, NLRP3, ASC, Caspase-1 mRNA and protein expressions and the degree of myocardial fibrosis were increased, but the cardiac function was decreased. Compared with DM group, there were no changes in total cholesterol and fasting blood glucose, the degree of myocardial fibrosis cardiac function was attenuated, NLRP3, ASC, Caspase-1 expressions, IL-1β and IL-18 levels were reduced in DM+Ir group. The results suggested that irbesartan may exert myocardial protection by inhibiting the expression of the NLRP3/ASC/Caspase-1 pathway in diabetic rats.